(untitled) (Damascus University Journal of educational and Psychologyical sciences, 2025)
Objectives: The study aimed to evaluate the level of academic alienation among Kuwait University students by analyzing three main dimensions: feelings of isolation and lack of belonging, loss of meaning and normlessness, and academic helplessness. It also sought to identify differences in alienation levels based on demographic variables (gender, academic major, nationality) and to provide recommendations to enhance the students’ academic experience. Methodology: The study employed a descriptive survey method, collecting data from 2,130 students using an electronic questionnaire. The sample represented approximately 7% of the student population, enabling a comprehensive analysis of academic alienation and its relationship with demographic variables. Findings: The study revealed that the level of academic alienation among Kuwait University students was generally moderate. The "loss of meaning and normlessness" dimension ranked highest, followed by "academic helplessness," and finally "feelings of isolation and lack of belonging." Significant differences were found between genders, with females experiencing higher levels of academic alienation. Additionally, students in applied sciences colleges exhibited higher levels of alienation compared to those in humanities colleges. The findings also indicated that non-Kuwaiti students reported higher levels of "loss of meaning and normlessness" compared to their Kuwaiti counterparts. Recommendations: Enhance the connection between academic curricula and the job market through practical applications and professional projects. Organize university activities that promote social integration and reduce isolation. Provide psychological and social support programs for female and non-Kuwaiti students to facilitate their adaptation to the university environment. Strengthen the role of students in academic decision-making to increase their sense of empowerment and engagement.